DEVELOPMENT STRATEGY OF HUMAN CAPITAL OF PT KIMIA FARMA (PERSERO) TBK - Arifin, Antoni Ludfi (IJHCM (International Journal of Human Capital Management), 2017)
This research is a qualitative research with case study at PT Kimia Farma (Persero) Tbk. The purpose of this research is to understand the overall development strategy of human capital of the Company. Data were collected from primary data through interview, observation, and recording; while secodary data were obtained from PT Kimia Farma (Persero) Tbk or from the externals that are used by the researcher to strengthen the premise, theory building, or data from previous researchers. The data collected from primary and secondary sources are then processed. The validity of data is checked though data accuracy checking process (triangulation). This research found that the Company has conducted human reseource development strategy through 1) Integrated HR Development with the Company’s visions and missions; 2) open recruitment and selection process will decide and find the candidates who meet the qualifications; 3) preparing assessement center to select the right candidate for the right position; 4) employees training can improve the employees’ competence; and 5) the right development of human capital to prepare for the competitiveness in the future.. Keywords: Human Capital, Development, Strategy, HR Planning